(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
From the mid-eleventh century onwards, Europe has seen a significant increase in the construction with durable materials (stone and brick), no longer reserved to a few, large, construction sites. It was a structural transformation, linked to the emergence of new individual, social and territorial identities. The Petrifying Wealth project – presented in the contribution – aims to investigate this process within Mediterranean Europe (Spain, southern France, Italy). This project has received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 695515